ANALISIS UNSUR INTRINSIK DAN NILAI MORAL DALAM CERPEN “PENA” KARYA RIKA - fitriana fitriana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Literary work is not only a word for word series that has aesthetic value, but also talks about the values of life. To understand the value contained in literary works, readers need to read, know, and analyze the elements in these literary works. One of the literary works that will be analyzed by the researcher is a short story entitled Pena by Rika. This research was conducted with the aim of describing the intrinsic elements in the short story Pena and describing the moral values contained in the short story. The research approach used in this research is descriptive qualitative using structural methods and content analysis strategies. The data source used is a collection of selected short stories Kompas 2017. With data collection steps; (1) reading the short story "Pena" intensively, (2) analyzing the cohesiveness of the short story's intrinsic elements and describing it, (3) analyzing the moral elements the writer wants to convey in the short story and describing it. The conclusions of this study are: (1) the intrinsic elements contained in the short stories of the Pena from the Compass Selected Short Story Collection 2017 include plot, setting, theme, characterization, point of view, mandate, and language style. (2) moral values contained in the short stories Pena from the Compass Selected Short Story Collection 2017.